Disparity between Preoperative and Pre-Excisional Intraoperative Parathyroid Hormone in Parathyroid Surgery - Masood, Maheer M.; Hackman, Trevor G. (International Archives of Otorhinolaryngology, 2018)
Introduction Intraoperative parathyroid hormone (ioPTH) testing is a widely accepted standard for assessing the parathyroid gland function. A decline of preoperative parathyroid hormone (PTH) levels by more than 50% is one accepted measure of parathyroid surgery adequacy. However, there may be a variation between preoperative PTH levels obtained at a clinic visit and pre-excisional ioPTH.Objective Our study explores the differences between preoperative PTH and pre-excisional ioPTH levels, and the potential impact this difference has on determining the adequacy of parathyroid surgery.Methods A retrospective study that consisted of 33 patients that had undergone parathyroid resection between September 2009 and March 2016 at a tertiary academic center was performed. Each subject's preoperative PTH levels were obtained from clinic visits and pre-excisional ioPTH levels were recorded along with the time interval between the measurements.Results There was a significant difference between the mean preoperative PTH and the pre-excisional ioPTH levels of 147 pg/mL (95% confidence interval [CI] 11.43 to 284.47; p = 0.0396). The exclusion of four outliers revealed a further significant difference with a mean of 35.09 pg/mL (95% CI 20.27 to 49.92; p < 0.0001). The average time interval between blood draws was 48 days + 32 days. A weak correlation between the change in PTH values and the time interval between preoperative and pre-excision blood draws was noted (r2 = 0.15).Conclusion Our study reveals a significant difference between the preoperative PTH levels obtained at clinic visits and the pre-excisional intraoperative PTH levels. We recommend routine pre-excisional intraoperative PTH levels, despite evidence of elevated preoperative PTH levels, in order to more accurately assess the adequacy of surgical resection.
Keywords: parathyroidectomy; parathyroid hormone; parathyroid neoplasms